Alpha‐Synuclein Oligomers and Neurofilament Light Chain in Spinal Fluid Differentiate Multiple System Atrophy from Lewy Body Synucleinopathies. Issue 3 (1st August 2020) - Singer, Wolfgang; Schmeichel, Ann M.; Shahnawaz, Mohammad; Schmelzer, James D.; Boeve, Bradley F.; Sletten, David M.; Gehrking, Tonette L.; Gehrking, Jade A.; Olson, Anita D.; Savica, Rodolfo; Suarez, Mariana D.; Soto, Claudio; et al.
Abstract : Objective: To explore the role of alpha‐synuclein (αSyn) oligomers and neurofilament light chain (NFL) in cerebrospinal fluid (CSF) as markers of early multiple system atrophy (MSA) and to contrast findings with Lewy body synucleinopathies. Methods: In a discovery cohort of well‐characterized early MSA patients (n = 24) and matched healthy controls (CON, n = 14), we utilized enzyme‐linked immunosorbent assay to measure NFL and protein misfolding cyclic amplification (PMCA) to detect αSyn oligomers in CSF. We confirmed findings in a separate prospectively enrolled cohort of patients with early MSA (n = 38), Parkinson disease (PD, n = 16), and dementia with Lewy bodies (DLB, n = 13), and CON subjects (n = 15). Results: In the discovery cohort, NFL was markedly elevated in MSA patients, with perfect separation from CON. αSyn‐PMCA was nonreactive in all CON, whereas all MSA samples were positive. In the confirmatory cohort, NFL again perfectly separated MSA from CON, and was significantly lower in PD and DLB compared to MSA. PMCA was again nonreactive in all CON, and positive in all but 2 MSA cases. All PD and all but 2 DLB samples were also positive for αSyn aggregates but with markedly different reaction kinetics from MSA; aggregation occurred later, but maximum fluorescence was higher, allowing for perfect separation of reactive samples between MSA and Lewy body synucleinopathies. Interpretation: NFL and αSyn oligomers in CSF faithfully differentiate early MSA not only from CON but also from Lewy body synucleinopathies. The findings support the role of these markers as diagnostic biomarkers, and have important implications for understanding pathophysiologic mechanisms underlying the synucleinopathies. ANN NEUROL 2020;88:503–512